Continuous professional learning in private higher education: Making a case for distributed leadership - Cronje, F.; Bitzer, E.M. (South African Journal of Higher Education, 2019)
Literature on management of professional learning in South African private higher education (PHE) institutions is limited. This may be due to incentives for professional learning in private higher education not being highly revered. Our paper reports on the findings of research conducted on four campuses of a South African private higher education provider, inquiring into broadening organisational leadership roles towards distributed leadership. Findings show that academic managers in PHE see the proper educational induction of academics as a contributing factor to professional and institutional cohesion. However, the role of academic managers in designing custom made professional learning initiatives is pivotal. Our findings confirm that academic managers in PHE contexts need to spend considerable effort on strategising their campus programmes to empower academic leaders through distributed leadership and with agency to lead their teams. We suggest a course of action for enhancing continuous professional learning (CPL) for academic staff in PHE: Firstly, academic management positions should be filled with the most competent people; secondly, academic managers should be directly accountable for the quality of professional learning on their campuses; and thirdly, academic managers need increased agency to use resources such as monetary and other incentives to support their academic teams.